Qualitative analysis of services in Astan Quds’ special library of Hadith and Quranic sciences: A LibQUAL study - Fatemeh Sahraei; Ali Akbar Khasseh (کتابداری و اطلاع‌رسانی, 2016)
Purpose: Specialized Library of Quran and Hadith Studies of Astan Quds Razavi plays a crucial role in providing specialized services to the research community. Therefore, evaluating the service quality and awareness from users’ perspective can help managers improve and provide higher quality services. Methodology: This research is a survey. Data were collected by the Libqual International questionnaire. The research population consisted of all members of the Central Library (141633 members) who user the specialized Library of Quran and Hadith Studies (except for children). 384 participants were selected by simple random sampling. Data were analyzed using SPSS version 19. Findings: According to the dimensions of Libqual, the “effectiveness of the library” (7.78) corresponds with the least expectations but is far from the maximum expected. “Control Information” (7.65) and “the library as a place” (7.7) correspond to the minimum and maximum services expected. Conclusion: The total average of the LibQual dimensions corresponds approximately with the minimum level of expectations it also corresponds fairly with the maximum level of user expectations.